Outcomes of transplant recipients treated with cidofovir for resistant or refractory cytomegalovirus infection. Issue 3 (2nd December 2020) - Mehta Steinke, Seema A.; Alfares, Mona; Valsamakis, Alexandra; Shoham, Shmuel; Arav‐Boger, Ravit; Lees, Laura; Ostrander, Darin; Forman, Michael S.; Shedeck, Audra; Ambinder, Richard F.; Jones, Richard John; Avery, Robin K.
Abstract: Background: Treatment of ganciclovir‐resistant (GCV‐R)/refractory cytomegalovirus (CMV) infections in blood/marrow transplant (BMT) and solid organ transplant (SOT) recipients remains suboptimal. Cidofovir (CDV), a nucleotide analogue with anti‐CMV activity, is nephrotoxic and oculotoxic. Methods: We retrospectively evaluated the outcomes of SOT and BMT patients with GCV‐R/refractory CMV treated with CDV between 1/1/2008 and 12/31/2017. Data collected: baseline demographics, CMV serostatus, clinical and virologic presentations and outcomes, UL97 and UL54 genotype mutations, drug toxicities, and cause of death. Descriptive statistics were used. Results: 16 patients received CDV for treatment of CMV: six BMT and 10 SOT. Seven (47%) of the patients had high‐risk donor/recipient serostatus: six (60%) SOT were D+/R‐; one (16.7%) BMT was D−/R+. Median time to CMV DNAemia was 131 days post‐transplant (IQR, 37.5‐230.3). Proven tissue invasive disease was present in three patients (18.8%). Twelve (75%) had genotype testing; 10 (83.3%) of those had antiviral resistance mutations. While on CDV, six (37.5%) developed nephrotoxicity, and four (25%) developed uveitis (two had both uveitis and nephrotoxicity). Eight (50%) had failure to clear CMV DNAemia despite CDV treatment. Eight (50%) of the patients died; median time to death, after initiation of CDV, was 33.5 days [IQR22‐988]. Conclusions: In the absence of good therapeutic alternatives, CDV is used in GCV‐R/refractory CMV infection. However, it is associated with a substantial risk of toxicity and failure to clear CMV DNAemia, highlighting the need for development of newer and less toxic therapies. The high mortality in this group of patients underscores the severity of illness in this population.